G41(P) Do hospitals provide a healthy diet for growing children?. (27th April 2016) - Gunatilleka, K; Jayatunga, R
Abstract : Aim: Healthcare professionals constantly emphasise the importance of a healthy diet. This audit intended to find out if this advice is practiced in hospital. Under or overnutrition in children can lead to consequences including obesity and constipation, which may contribute to a longer hospital stay. Obesity is a rapidly growing epidemic in the UK, with 31% of children being overweight or obese in 2014. The 2004 Children's National Service Framework emphasised the need to provide a healthy diet in hospital. We aimed to analyse the menus provided to children on paediatric wards in a deprived inner city hospital. An audit conducted in 2006 at this hospital found that 50% of food chosen was fried food, and that one child ate chicken nuggets every day for 6 weeks! Method: The menus from two paediatric wards were collected in October 2014. Patients aged 18 months to 16 years were included. 187 menus were analysed to find out: What food was on offer Whether these options were healthy What food was chosen Who chose the food (child/parent/staff)? Results: For lunch the most popular choice was ham sandwiches. Chicken nuggets were the most popular dinner choice, with 60% of children choosing a fried meal. 75% of children chose a meat or fish option, whereas options containing vegetables were seldom chosen. For sides, salads were rarely ordered by both children and staff, whereas crips, quavers and wotsits were chosen 50% of the time by children and 75% of the time by staff (for children). Potatoes were the most popular side, with chips being twice as popular as mash. The only fruit options available were apples, oranges and bananas. Staff chose fruit more often than children for dessert. The most popular desserts were bananas, ice cream and yoghurt. Conclusion: This study suggests that children do not receive a healthy diet in hospital. Healthy diets should be introduced while in hospital to develop an awareness of healthy eating, especially if obese. The final objective is to ensure that children meet their nutritional requirements, allowing for a quicker recovery and discharge from hospital.